Habitat connectivity modeling for urban conservation planning: A case study of pileated woodpecker (Dryocopus pileatus) in Hamilton County, Ohio, USA - Ruijia Hu; Susanna T.Y. Tong (Ecological Indicators)
Urban forests provide vital wildlife habitats, but as urbanization intensifies and tree resources dwindle, these habitats are becoming more limited and fragmented. Given the meager resources available for wildlife habitat conservation, there is a pressing need for affordable, user-friendly tools and indicators to help in the prioritization and optimization of habitat conservation efforts and in aligning habitat accessibility with broader conservation objectives. The aim of our study is to provide an approach to assess the importance of including small habitat unites (stepping stones) as an indicator of overall habitat availability and accessibility for a forest bird species, Dryocopus pileatus (Pileated Woodpecker, PIWO), in Hamilton County, Ohio, U.S.A. To improve ecological relevance in our approach, we integrated PIWO’s presence location data with detailed resource-based variables, as well as land use and land cover data, to better account for the heterogeneity in habitat quality and species distribution within land classes. To garner broader support from local communities for wildlife habitat conservation, we considered the diverse benefits of conservation projects by integrating landscape graph analyses with land acquisition decisions. This approach helped us identify large habitat patches and small habitat units that meet the PIWO’s habitat requirements and evaluate how individual habitat patches/units, both existing and new, contribute to overall habitat availability and connectivity. The small stepping stones we identified could form least-cost corridors that connect large habitat patches, thereby enhancing species’ accessibility to forest resources and promoting its long-distance dispersal across the landscape. This suggests the importance of stepping stones and habitat connectivity in PIWO conservation. The loss of these stepping stones would significantly hinder conservation efforts and be difficult to offset. We found that by incorporating local planning objectives in this analysis, potential land acquisition sites that can enhance ecological services and improve habitat connectivity and accessibility can be easily identified. These results are instrumental in preservation and reforestation efforts.